This Examined Life: The Upside of Self-Knowledge for Interpersonal Relationships - Tenney, Elizabeth R.; Vazire, Simine; Mehl, Matthias R. (PLOS ONE, 2013)
Although self-knowledge is an unquestioned good in many philosophical traditions, testing this assumption scientifically has posed a challenge because of the difficulty of measuring individual differences in self-knowledge. In this study, we used a novel, naturalistic, and objective criterion to determine individuals’ degree of self-knowledge. Specifically, self-knowledge was measured as the congruence between people’s beliefs about how they typically behave and their actual behavior as measured with unobtrusive audio recordings from daily life. We found that this measure of self-knowledge was positively correlated with informants’ perceptions of relationship quality. These results suggest that self-knowledge is interpersonally advantageous. Given the importance of relationships for our social species, self-knowledge could have great social value that has heretofore been overlooked.